Proceso de atención de enfermería en paciente pediátrico con crisis convulsiva por encefalitis. - Morocho Chango, Jeaneth Marisol (2018)
The present clinical case is based on a pediatric patient entering the emergency area of the General Teaching Hospital of Calderón for presenting a clinical picture: headache, hyperthermia, memory disorders, and presenting tonic-clonic convulsive seizures of a short second duration . Encephalitis is an inflammatory process that mainly affects the central nervous system. Committing the brain. Causing clinical pictures of neurological disorders, due to multiple etiological agents, mainly viruses, which may in other cases affect the brain (encephalitis) or the spinal cord (myelitis or encephalomyelitis). This disease causes a high morbidity and mortality rate if it is not detected in time. The process of nursing care and the 5 stages of nursing were applied to the user. As it is the assessment of the needs of the patient, by means of the cephalo caudal physical examination, neurological examination and by the functional patterns of Marjory Gordon and in this way identify the real or potential problems.